DIAGNOSTIC ACCURACY OF IMAGING IN THE DETECTION OF ACUTE PANCREATITIS IN THE POSTOPERATIVE PATIENT - Mustafayev, A.N. (World of Medicine and Biology, 2024)
The purpose of the work was to improve the diagnostic results of acute postoperative pancreatitis through the use of computed tomography. The study included 60 patients aged from 30 to 50 years and older. All patients underwent analysis of data from ultrasound, computed tomography. In the study cohort of patients, patients predominated after undergoing surgery in the area of the pancreas itself, on the organs of the hepatic-pancreatic-biliary zone. Ultrasound confirmed the diagnosis of acute postoperative pancreatitis in 27 patients, and computed tomography data confirmed acute pancreatitis in 36 cases. Among patients with positive ultrasound results, in 22 they were true positive and in 5 they were false positive. Among the 33 patients with negative ultrasound results, 2 were false-negative, while 31 were true-negative. The sensitivity and specificity of ultrasound in diagnosing postoperative acute pancreatitis, using computed tomography as the gold standard, was 91.7 %, 86.1 %.